FISHING STRATEGY OF THE INDONESIAN TUNA LONGLINERS IN INDIAN OCEAN - Lilis Sadiyah; Budi lskandar Prisantoso (Research Center for Fisheries, 2011)
Information on fishing strategy is essential to manage the Indonesian tuna fishery. Therefore, it is important to attempt to characterise the fishing strategies of the fishery.